1991
DOI: 10.1161/01.hyp.17.1_suppl.i182
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium reduction for hypertension prevention and treatment.

Abstract: Nutritional-nonpharmacological approaches for the treatment and prevention of hypertension are of great interest Sodium reduction is one of the primary methods recommended for these purposes. The general public is interested in the redaction of dietary sodium intake and has responded with a decrease in table salt use, the purchase of lowered sodium food products, and the use of food labels to help guide food purchases. Countervailing trends in the use of convenience foods and dining out increase the difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In their study, 39% of free living subjects achieved the urinary sodium excretion level of less than 74 mmola24 h corresponding to a salt intake of ®ve grams or less per day. Some clinical trials have demonstrated the feasibility of reducing sodium intake to levels of 70 ± 100 mmoladay for up to 4 y (Elmer et al, 1991). In our study 47% of women attained the 24-h sodium excretion of 74 mmol.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In their study, 39% of free living subjects achieved the urinary sodium excretion level of less than 74 mmola24 h corresponding to a salt intake of ®ve grams or less per day. Some clinical trials have demonstrated the feasibility of reducing sodium intake to levels of 70 ± 100 mmoladay for up to 4 y (Elmer et al, 1991). In our study 47% of women attained the 24-h sodium excretion of 74 mmol.…”
Section: Discussionsupporting
confidence: 55%
“…In the study by Alli et al (1992) dietary advice was given by general practitioners not by nutritionists. Furthermore, single short counselling sessions with advice on salt restriction have not been successful in producing dietary changes (Elmer et al, 1991), and thus more comprehensive nutrition and behavior oriented programs that provide follow-up contacts are needed to achieve signi®cant sodium reduction in clinical settings. In the present study, the acceptance of salt restriction were strengthened by the supply of low salt bread and regular follow-up contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,24 The baseline sodium excretion of TOHP II participants was 187 mmol/day, consistent with data from other trials. 6,25 In the TOHP II population, the BP response estimated in Figure 4 could have been achieved with an average decrease in sodium intake of approximately 53% (100 mmol). This level of sodium reduction is not infeasible, and could have a positive impact on overall public health.…”
Section: Discussionmentioning
confidence: 99%
“…The level of sodium reduction in TOHP II approximates the maximum that can be achieved and maintained by individuals making food selections in the community even when these individuals are highly motivated and extensively counseled. 4,5,[34][35][36] Even the relatively modest level of sodium reduction observed in TOHP II is unlikely to be attained in the general US population without changes in the food supply.…”
Section: Public Health Implicationsmentioning
confidence: 99%